An Epidemiological study of mental illness (Hospital Bahagia, Ulu Kinta, perak) / Jaffar Othman - Jaffar, Othman (1973)
One of the most disturbing social problems in the world today is mental illness, Though it is not so serious in developing and underdeveloped countries but in countries which are well advanced and highly developed this problems has turned out to be very serious indeed. In the United States alone, there are approximately 750,000 persons who are hospitalised in mental institutions (1957) and they occupy some 55% of all hospital beds. In Malaysia, today, this problem is not very serious yet. Though in the past we are not clearly aware about it, today the situation has changed. The Government had spent millions of dollars in trying do deal with it. In Hospital Bahagia alone an amount of $1,025,000 has been allocated for expenditure during the Second Malaysia Plan (Annual Report, Hospital Bahagia 1971).